A Brief Comparison of Physical Education and Sport within the Czechoslovak and Polish YMCA in the Interwar Years - Tomáš Tlustý (Jan Długosz University in Częstochowa, 2019)
This paper looks at the history of physical education and sports in the Czechoslovak and Polish YMCA. As far as physical education and sports are concerned, the two national associations not only developed in a similar way but cooperated in some areas of their activity as well. The two associations were established and began to work together in the 1920s, exchanging printed matter or arranging friendly matches. In the course of time, both of these national associations began to build their own premises equipped with modern sports facilities and their members participated in matches on a regular basis. The origin of the YMCA and the source of money flowing into Czechoslovakia and Poland led to restrictions being placed on both of these national associations as the outbreak of the Second World War drew near. They were later dissolved and were not fully reestablished until the 1990s.